Sulfur Metabolism Pathways in Sulfobacillus acidophilus TPY, A Gram-Positive Moderate Thermoacidophile from a Hydrothermal Vent - Guo, Wenbin; Zhang, Huijun; Zhou, Wengen; Wang, Yuguang; Zhou, Hongbo; Chen, Xinhua (Frontiers in Microbiology, 2016)
Sulfobacillus acidophilus TPY, isolated from a hydrothermal vent in the Pacific Ocean, is a moderately thermoacidophilic Gram-positive bacterium that can oxidize ferrous iron or sulfur compounds to obtain energy. In this study, comparative transcriptomic analyses of S. acidophilus TPY were performed under different redox conditions. Based on these results, pathways involved in sulfur metabolism were proposed. Additional evidence was obtained by analyzing mRNA abundance of selected genes involved in the sulfur metabolism of sulfur oxygenase reductase (SOR)-overexpressed S. acidophilus TPY recombinant under different redox conditions. Comparative transcriptomic analyses of S. acidophilus TPY cultured in the presence of ferrous sulfate (FeSO4) or elemental sulfur (S0) were employed to detect differentially transcribed genes and operons involved in sulfur metabolism. The mRNA abundances of genes involved in sulfur metabolism decreased in cultures containing elemental sulfur, as opposed to cultures in which FeSO4 was present where an increase in the expression of sulfur metabolism genes, particularly sulfite reductase (SiR) involved in the dissimilatory sulfate reduction, was observed. SOR, whose mRNA abundance increased in S0 culture, may play an important role in the initial sulfur oxidation. In order to confirm the pathways, SOR overexpression in S. acidophilus TPY and subsequent mRNA abundance analysis of sulfur metabolism-related genes were carried out. Conjugation-based transformation of pTrc99A derived plasmid from heterotrophic E. coli to facultative autotrophic S. acidophilus TPY was developed in this study. Transconjugation between E. coli and S. acidophilus was performed on modified solid 2:2 medium at pH 4.8 and 37°C for 72 h. The SOR-overexpressed recombinant S. acidophilus TPY-SOR had a SO42−-accumulation increase, higher oxidation/ reduction potentials (ORPs) and lower pH compared with the wild type strain in the late growth stage of S0 culture condition. The transcript level of sor gene in the recombinant strain increased in both S0 and FeSO4 culture conditions, which influenced the transcription of other genes in the proposed sulfur metabolism pathways. Overall, these results expand our understanding of sulfur metabolism within the Sulfobacillus genus and provide a successful gene-manipulation method.